Kajian sosio-ekonomi selepas kemasukan industri pembalakan dan perlaksanaan Projek hidro-elektrik Bakun: Kajian kes di Uma Bawang Murum - Juan, Ubit (Universiti Malaysia Sarawak (UNIMAS), 1997)
There is fairly wiespread view that the people of the interior, the Orang Ulu, are a low-income and poverty group. However, there are actually no studies, besides periodic income surveys based upon respondent recall of income over a period of time., the income of this communities is based on a variety of activities which change from month to month. Hence, a survey requiring people to recall their income over a period of time is likely unreliable. The main aim of this study is to attempt a different method. It tracks a small sample of hauseholds daily for a month. Respondents are prorated daily for their income and expenditure during the previous day. This sample was drawn from the Kayan longhuse of Uma Bawang at Long Murum in the district of Belaga. Given the nature of this study and the time constraints, the study of income and expenditure could only be conducted for one month. This is a significant weakness as incomes and expenditure varies seasonally. Researcher is confident that the income figures obtained are accurate, at least for the period of the study. The striking findings of this study are: " While there is a range of incomes, none of the sample households is in poverty; " The sources of income have changed drastically recently, with wages forming the largest component of income; " Agricultural work and activities based on resource extraction have shrunk. This is not an indication of an abandonment of agriculture and farm work. It is a result of the arising of logging industry, The recent events, essentially the launching of the Bakun Hydroelectric Project, have resulted in considerable uncertainty on the part of the members of Uma Bawang.